MODELING AND VALIDATION OF CO-TORREFACTION KINETICS OF MACRO PARTICLE FOR HYBRID COAL PRODUCTION - Setiawan, Sendi
Co-torrefaction between low-rank coal and biomass can produce new solid fuels, namely hybrid coal, and become an alternative to take advantage of the use of biomass (waste) and improve the quality of low-rank coal. This study aims to obtain a kinetic model to describe the co-torrefaction process of hybrid coal. A mixture of sub-bituminous coal (70%-mass) and pine sawdust biomass (30%-mass) is used as feedstock that becomes one particle. The hybrid coal model (macro particle) is built from the integration of kinetic models with heat transfer models. Modeling using the DAEM kinetics model produced a mass reduction model relative to temperature increase that correlated well with the TGA analysis data of coal and biomass mixtures with a correlation coefficient (R2) of 0.99240. Macro particles built from the integration of kinetic model and heat transfer model produce mass yield distribution models at temperatures of 200°C, 260°C, and 300°C that resemble experimental data from hybrid coal co-torrefaction processes with an average error value of 4.93%. Based on the simulation results, particle size, temperature, and cotorrefaction time affect the mass yield distribution of hybrid coal. At a temperature of 300°C and a co-torrefaction time of 43 minutes, a particle with a radius of 3 cm resulted in a mass yield of 85%, while a particle with a radius of 2 cm resulted in a mass yield of 78.96%. At 100 minutes and a particle size of 1 cm, the mass yield value produced for a temperature of 300°C is 77.32%, while at a temperature of 200°C the mass yield is 95.51%. At a temperature of 260°C and a particle size of 1 cm, a co-torrefaction time of 20 minutes resulted in a mass yield of 86.49%, while a co-torrefaction time of 40 minutes resulted in a mass yield of 85.85%. The resulting model can be used to predict the mass yield of hybrid coal under various conditions of particle size, temperature, and cotorrefaction time.